2019
DOI: 10.4049/jimmunol.1801276
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic and Arthritogenic Properties of the Soluble Form of CD13

Abstract: Aminopeptidase N/CD13 is expressed by fibroblast-like synoviocytes (FLS) and monocytes (MNs) in inflamed human synovial tissue (ST). This study examined the role of soluble CD13 (sCD13) in angiogenesis, MN migration, phosphorylation of signaling molecules, and induction of arthritis. The contribution of sCD13 was examined in angiogenesis and MN migration using sCD13 and CD13-depleted rheumatoid arthritis (RA) synovial fluids (SFs). An enzymatically inactive mutant CD13 and intact wild-type (WT) CD13 were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…The potential importance of NAP is related to its expression by fibroblast-like synoviocytes in inflamed synovial tissue in humans, suggesting a role in acute inflammatory arthritis. 29 Regarding PSA, while there is a paucity of data, spinorphin, an endogenous enzyme inhibitor, has been reported to break down enkephalin and play a role in pain and inflammation. 44 The possible role of PSA in pain strengthens its clinical relevance, in that, as underlined by scientific societies, pain is an important clinical feature in deciding whether to indicate arthroplasty, and this is what motivated us to include it in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential importance of NAP is related to its expression by fibroblast-like synoviocytes in inflamed synovial tissue in humans, suggesting a role in acute inflammatory arthritis. 29 Regarding PSA, while there is a paucity of data, spinorphin, an endogenous enzyme inhibitor, has been reported to break down enkephalin and play a role in pain and inflammation. 44 The possible role of PSA in pain strengthens its clinical relevance, in that, as underlined by scientific societies, pain is an important clinical feature in deciding whether to indicate arthroplasty, and this is what motivated us to include it in our study.…”
Section: Discussionmentioning
confidence: 99%
“…aminopeptidase N, expressed by fibroblast-like synoviocytes) are present in synovial fluid and could play a role in OA. 29 As de Silveira et al 30 demonstrated, in an animal model of arthritis, joint inflammation was induced by activation of the renin-angiotensin system, but reduced by activation of angiotensin-converting enzyme-2/Ang-(1–7)/Mas receptor pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Ab-mediated cross-linking of CD13 in mast cells leads to IL-6 production (82). Additionally, soluble CD13 is highly abundant in synovial fluid of rheumatoid arthritis patients, where it increases expression of proinflammatory cytokines (83)(84)(85)(86)(87)(88)(89)(90). With regard to HCoV-229E infection, treatment of primary human nasal and tracheal epithelial cells with glycopyrronium/formoterol/budesonide, a mixture of drugs used to treat chronic obstructive pulmonary disease caused by HCoV-229E infection, led to reduced CD13 expression, fewer acidic endosomes that are essential for the entry of HCoV-229E, as well as decreased production of inflammatory cytokines (79).…”
Section: Cd13/apn/anpep Inflammation and Il-6mentioning
confidence: 99%
“…CD13 can also be shed from the cell membrane by MMP-14 (25), and the resultant sCD13 functions by engaging GPCRs on cytokine-activated lymphocytes (19), MNs, ECs, and fibroblasts (26). However, the identity of such GPCRs has not CD13 also tethers the IQGAP1-ARF6-EFA6 complex on the plasma membrane to promote ARF6 activation, b1 integrin recycling, and cell migration.…”
Section: Mechanisms Of Cd13 Functionsmentioning
confidence: 99%
“…yet been reported. With binding to GPCRs, sCD13 induces phosphorylation of Src, ERK1/2, and, to some extent, NF-kB, activating cell migration, angiogenesis, and other responses (26). Pertussis toxin, a GPCR inhibitor, significantly reduced chemotactic responses of cytokine-activated T cells (19) or monocytic cells as well as endothelial capillary morphogenesis in response to sCD13 (26).…”
Section: Mechanisms Of Cd13 Functionsmentioning
confidence: 99%